Using irAOP for non-clinical safety evaluation of biotechnology-derived pharmaceuticals and ATMPs: a paradigm shift into a systematic and holistic framework - Armin Braun; Susann Dehmel (Journal of Immunotoxicology)
The chances and opportunities in modern biology inspired devising new therapeutics are mind blowing. The promises reach from successfully treating so-far incurable diseases like cancer and certain infections, to modulating and fine tuning the immune response to prolong the lifespan by inhibiting aging. However, as underlying therapies become more and more complex and sophisticated, it becomes increasingly difficult to find ways to ensure and predict the safety of these new therapeutics. The ICH guideline S6 (R1) from June 2011 EMA/CHMP/ICH/731268/ 1998 Committee for Medicinal Products for Human Use (CHMP) already stated “Conventional approaches to toxicity testing of pharmaceuticals may not be appropriate for biopharmaceuticals due to the unique and diverse structural and biological properties of the latter that may include species specificity, immunogenicity, and unpredicted pleiotropic activities” and is committed to a “flexible, case-by-case, science-based approach to preclinical safety evaluation”. Initial approaches to this are described in the OECD Test Guidelines for new approach methods (NAM) with the newest update released in 2023 and alternative non-animal test guidelines (https://www.icapo.org/test-guidelines) provided from the International Council on Animal Protection in OECD Programmes (ICAPO; https://www.icapo.org). Beyond that, the European Union-funded innovative medicine initiative project Immune Safety Avatar (imSAVAR) decided to develop a systematic and holistic framework for non-clinical safety assessment of biopharmaceuticals and Advanced Therapy Medicinal Products (ATMP); thereby, the consortium focuses on immuno-regulatory therapeutics. Science-based approaches, such as the mechanistic description of adverse outcomes would be essential to demonstrate the safety of a particular new immuno-therapeutic agent. Here, we re-use the concept of adverse outcome pathways (AOP) to capture immune-related adverse outcomes (irAO), which are aimed to guide us to the use of relevant test systems and experiments. Thus, the focus within imSAVAR is on the use and (further) develop-ment of human and alternative models.